An empirical analysis of the factors affecting social entrepreneurial intentions - Preeti Tiwari; Anil K. Bhat; Jyoti Tikoria (Journal of Global Entrepreneurship Research, 2017)
The present study aims at identifying the social entrepreneurial intention among undergraduate students in Indian context by using the theory of planned behaviour as the research framework. A 72 item questionnaire was responded by 390 students of premier technical universities of India. A method of sampling used was systematized random sampling. 69% (N = 269) of the respondents were male and 31% (N = 121) were female and the average age of the respondents was approximately 20 years. The questionnaire measured emotional intelligence, creativity, and moral obligation, attitude toward becoming a social entrepreneur, subjective norms and perceived behavioural control. The result shows that the proposed model in the present study explains 47% of the variance, explaining the social entrepreneurship intention. Creativity showed a strongest positive relationship followed by emotional intelligence. This research study contributes to the social entrepreneurship literature by introducing emotional intelligence and creativity as new antecedents that also explains social entrepreneurial intention formation.
Keywords: 650; Emotional intelligence; Creativity Moral obligation; The theory of planned behaviour; Social entrepreneurship Intentions